A STUDY OF SPEECH ACTS: PERLOCUTIONARY ACTS IN “THE THURSDAY MURDER CLUB” MOVIE - Stefanie Hasianna Natania Sagala; Rizka Amalia; Amelia Az-zahra Dalimunthe; Hikmah Alya (ELITERATE : Journal of English Linguistics and Literature Studies, 2025)
Language plays a crucial role not only in conveying information but also in influencing others through speech, which makes the study of speech acts essential in understanding communication both in real life and in fictional contexts. While previous studies have widely examined locutionary and illocutionary acts, research focusing on perlocutionary acts, particularly in film dialogue, remains limited, leaving a gap in understanding how language in media elicits emotional or behavioral responses from audiences and characters. Therefore, this study aims to analyze the types of perlocutionary acts used in the movie The Thursday Murder Club based on Austin’s Speech Act Theory and Leech’s classification of perlocutionary effects. Using a qualitative descriptive method, the researchers identified and categorized selected utterances from the film’s dialogues into six perlocutionary types: persuade, encourage, irritate, deceive, attract action, and embarrass. The results show that persuasive acts are the most dominant, followed by irritation and encouragement, indicating that most dialogues are designed to influence and evoke emotional reactions among characters while maintaining the movie’s crime-comedy tone. These findings reveal that perlocutionary acts serve not only as linguistic expressions but also as narrative devices that enhance characterization, tension, and humor. In conclusion, this study underscores that language in film functions as a powerful medium for persuasion, emotion, and engagement, bridging the gap between linguistic theory and cinematic storytelling